Factors associated with abnormal cervical smears in HIV negative women in Soweto - Mntambo, Adolphus Qedusizi (My University, 2010)
Introduction: Cervical cancer is caused by persistent infection with high-risk Human Papilloma Virus (HPV) and is a leading cause of cancer deaths in South African women aged 15-65years. We estimated prevalence of abnormal (Atypical squmous cells of unknown significance to invasive cervical cancer) cervical cytology and associated cofactors in 18-35-year old women who tested negative for Human Immuno deficiency Virus (HIV). Method: This cervical lesion study was secondary analysis of data collected during a Microbicide Feasibility Study (MFS). MFS recruited 1100 women from public health care facilities. Women were interviewed and socio-demographic, sexual behaviour and clinical information was collected. If HIV negative, cervical and vaginal swabs were collected for Pap smear and laboratory testing for sexually-transmitted infections (STI). For the cervical lesion study, 808 women were eligible and 752 were enrolled in the study. Associations with abnormal cervical cytology were analysed using multiple logistic regression, and were reported as adjusted odds ratio (AOR) with a 95% confidence interval (CI). Results: We analysed 570 cytology specimens. Prevalence of abnormal cervical cytology was 6.7% (95% CI 4.8-9.0). Women who had an abnormal cervical cytology result were more likely than those with normal cytology results to report abnormal vaginal discharge (OR 2.33; 95% CI 1.07-5.06; p=0.03). They were also more likely to have more than one child (OR 2.21; 95% CI 1.00-4.87; p=0.05). v Discussion and conclusion: Our study showed that LSIL is common in this younger age group. Because HPV infection and thus abnormal cervical cytology are high among the younger population, this result is not unexpected. Since most LSIL regress naturally, our data support the current South African screening protocol for cervical cancer.
MPH, School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: abnormal cervical smears